REVEALING MILES’ MENTAL HEALTH ISSUES IN UGLY LOVE NOVEL THROUGH TRANSITIVITY SYSTEM - Annisa Fissilmi; Diah Supatmiwati; Zainudin Abdussamad (Universitas PGRI Sumatera Barat, 2025)
This study investigates the linguistic representation of mental health issues in the character Miles Archer from Colleen Hoover’s Ugly Love using the transitivity system of Systemic Functional Linguistics (SFL) and supported by psychoanalytic theory. A descriptive qualitative method was employed to analyze 1,171 clauses from Miles’ utterances, identifying six transitivity processes: relational, material, mental, verbal, behavioral, and existential. The findings reveal that relational processes dominate (31%), reflecting Miles’ fixation on identity and self-blame, followed by material (29.4%) and mental (29.1%) processes, which signify his emotional detachment and internal conflict. These linguistic patterns align with clinical traits of Post-Traumatic Stress Disorder (PTSD) and Major Depressive Disorder (MDD), as outlined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). The study concludes that transitivity analysis is a powerful tool for exploring mental health portrayals in fiction, offering interdisciplinary insights into how language encodes psychological distress.